Unusual osteolitic intraosseous ganglion cyst of the medial tibial condyle in a patient affected by mild osteoarthritis of the knee - Giardini, Piero; Menna, Carlo Raimondo; Barbareschi, Mattia; Molinari, Marco (Acta Biomedica Atenei Parmensis, 2020)
Bone lesion of the proximal tibia are common findings; depending on the site, age of the patient and symptoms a carefull differential diagnosis must be carried out. We present the case of a 60 years old active patient presenting at our clinic with atraumatic knee pain. X-Rays performed revealed an osteolitic lesion of the medial tibial condyle; MRI highlighted a lobulated cystic lesion of the medial tibial condyle without evidence of interruption of the suchondral bone. The cavity appeared with low signal intensity on T1 weighted images and with a high signal intensity on T2 images The tissue obtained from the incisional biopsy macroscopically revealed a clear, yellowish gelatinous and mucinous material; the microscopical hystological exam confirmed a cystic area of the lesion; the lumen contained some dense, fibrous matherial with focal mucoid degeneration, while the wall was composed of a fibrous tissue with rare ossification and calcification. Clinical history, imaging and histhological findings lead to a certain diagnosis of an intraosseous ganglion cyst. We decided to surgically treat the lesion with courettage and bone grafting with allograft;the anterior part of the deep medial collateral ligament was used to avoid the leakage of the transplanted bone. With limitations concerning the short follow up, we obtained an optimal result in terms of patients satisfaction; this result is mainly related to the relief of the pain and the possibility for the patient to return to his activities. An accurate follow up must be carried out to verify the integration of the allograft